ヒガシ ナンキョク ミズホ コウゲン デ カンソク サレタ レーダー タジュウ ハンドウ カラ モトメタ ガンバン ケイジョウ - 前, 晋爾; マエ, シンジ; MAE, Shinji (国立極地研究所, 1978)
P(論文) 日本南極観測隊はみずほ高原を中心に,電波氷厚計を用いて,氷厚の測定を行った.観測される電波エコーは,多重反射を示している. NARUSEとYOKOYAMAは,エコー時間の最も長いエコーを岩盤からの反射と仮定して,氷厚を計算した.しかし,岩盤の細い凸凹に起因するといわれている"spatial fading効果"によって,岩盤からりエコーの欠落が起こることが知られている.また,岩盤表面が大きなスケールで起伏している場合には,岩盤からのエコーよりもエコー時間の長いエコー,あるいは短いエコーが観測されることも知られている.したがって,上記の仮定はかならずしも正しくない.この論文では,上記の効果を考慮して多重反射エコーを総合的に解析し,より妥当な氷厚および岩盤形態を導き出した.みずほ高原の相当部分,少なくともルートA以北の大部分では,底面すべりが起こっており,底の岩盤上に水が存在することを考えて,得られた岩盤地形のある部分(図2のV-W谷)には,氷下湖の存在する可能性があることを示した. Taking into account the effect of spatial fading and erronous echoes caused by large scale undulations of bedrock surface, the radar echo data by the 14th Japanese Antarctic Research Expedition were reanalysed to obtain the ice thickness and bedrock topography in the Mizuho Plateau area. The bedrock topographies along three Routes A, C and S are drawn by solid lines in Figs. 3, 4 and 5 respectively. Even though slopes on the bedrock were smoothened, there remain some steep ones which satisfy the condition of the existence of a sub-ice water lake. Since it was expected from the data of surface velocity measurements along Route A that the basal sliding was taking placing with the ice sheet north of Route A in the Mizuho Plateau, it is probable that there exist a sub-ice water lake along the valley indicated by a dotted line V-W in Fig. 2. departmental bulletin paper